Coordinated Generation and Transmission Maintenance Scheduling Considering Network Constraints via GGDF and ODF - Hussin, S. M.; Hassan, M. Y.; Wu, L. (International Journal of Integrated Engineering, 2016)
This paper proposes a coordinated generation and transmission maintenance scheduling by incorporating network constraints. The main advantage of the proposed approach is that maintenance is scheduled at the optimal period of the lowest possible operating cost while satisfying all the specified constraints. In this approach, sensitivity factors (GGDFs and ODFs) which are based on DC approximation are applied to calculate the line flows in normal and maintenance conditions. They are applied due to their simplicity, linearity, physical comprehension and rapidity of computation. To simulate the effect of network constraint on maintenance schedule and operating cost, several cases are studied with and without transmission limit constraints. To ensure the accuracy of these sensitivity factors, power flows on each line are compared with the one obtained from a PSSE simulator. The result shows that generators and transmission lines are scheduled at periods that satisfy the transmission capacity limit.